Photothermal Catalysis: Targeting Activation of CO2 and H2 over Ru‐Loaded Ultrathin Layered Double Hydroxides to Achieve Efficient Photothermal CO2 Methanation in Flow‐Type System (Adv. Energy Mater. 5/2017). Issue 5 (March 2017) - Ren, Jian; Ouyang, Shuxin; Xu, Hua; Meng, Xianguang; Wang, Tao; Wang, Defa; Ye, Jinhua
Abstract : Activation of reactants plays a significant role in the highly‐efficient catalytic reaction. In article number 1601657, Shuxin Ouyang, Jinhua Ye, and co‐workers demonstrate a targeted strategy to effectively activate CO2 and H2 via the support of ultrathin layered double hydroxides and the Ru nanometal, respectively, which enables the photothermal CO2 reduction to run in a flow‐type system and therefore evolves CH4 with a high yield rate of 230.8 mol h −1 m −2 (irradiation area).